Mechanisms of Cisplatin-Induced Apoptosis and of Cisplatin Sensitivity: Potential of BIN1 to Act as a Potent Predictor of Cisplatin Sensitivity in Gastric Cancer Treatment. (12th June 2012) - Tanida, Satoshi; Mizoshita, Tsutomu; Ozeki, Keiji; Tsukamoto, Hironobu; Kamiya, Takeshi; Kataoka, Hiromi; Sakamuro, Daitoku; Joh, Takashi
Abstract : Cisplatin is the most important and efficacious chemotherapeutic agent for the treatment of advanced gastric cancer. Cisplatin forms inter- and intrastrand crosslinked DNA adducts and its cytotoxicity is mediated by propagation of DNA damage recognition signals to downstream pathways involving ATR, p53, p73, and mitogen-activated protein kinases, ultimately resulting in apoptosis. Cisplatin resistance arises through a multifactorial mechanism involving reduced drug uptake, increased drug inactivation, increased DNA damage repair, and inhibition of transmission of DNA damage recognition signals to the apoptotic pathway. In addition, a new mechanism has recently been revealed, in which the oncoprotein c-Myc suppresses bridging integrator 1 (BIN1), thereby releasing poly(ADP-ribose)polymerase 1, which results in increased DNA repair activity and allows cancer cells to acquire cisplatin resistance. The present paper focuses on the molecular mechanisms of cisplatin-induced apoptosis and of cisplatin resistance, in particular on the involvement of BIN1 in the maintenance of cisplatin sensitivity.